Mummy Induces Apoptosis Through Inhibiting of Epithelial-Mesenchymal Transition (EMT) in Human Breast Cancer Cells: - Yari Khosroushahi, Ahmad; Rahmani Barouji, Solmaz; Shahabi, Arman; Torbati, Mohammadali; Fazljou, Seyyed Mohammad Bagher (Galen Medical Journal, 2020)
Background: Mummy (Iranian pure shilajit) is a remedy with possessing anti-inflammatory, antioxidant and anticancer activities. This study aimed to examine mummy effects on epithelial-mesenchymal transition (EMT) and invasiveness of MCF-7 and MDA-MB-231 breast cancer (BC) cell lines with underlying its mechanism. Materials and Methods: The dose-dependent inhibitory effect of the mummy on cell proliferation in vitro was determined using the MTT assay. Flow cytometry and 4â€™,6-diamidino-2-phenylindole dihydrochloride staining were respectively used for quantitative and qualitative analysis of cellular apoptosis, and gene expression analysis was conducted using real-time PCR. Results: MDA-MB-231 showed more sensitivity than the MCF-7 cell line to the anticancer activity of mummy, while mummy did not exhibit significant cell cytotoxicity against human normal cells (MCF-10A). The gene expression profile demonstrated a significant decrease in TGF-Î²1, TGF-Î²R1, TWIST1, NOTCH1, CTNNB1, SRC along with an increase in E-cadherin mRNA levels in mummy treated cells compared to the untreated control group (Pâ‰¤0.05). Conclusion: Mummy triggers inhibition of EMT and metastasis in breast cancer cells mainly through the downregulation of TGFÎ²1 activity, and more studies required to find its specific anticancer activity with details. [GMJ.2020;9:e1812]